Implication of Dichomitus squalens manganese-dependent peroxidase in dye decolorization and cooperation of the enzyme with laccase - Susla, M; Novotný, C; Erbanová, P; Svobodová, K (Folia microbiologica, 2008)
Three new chromatographic forms of Dichomitus squalens manganese-dependent peroxidase (MnP) were isolated from wheat-straw cultures using Mono Q and connective interaction media (CIM) fast protein liquid chromatography. Enzymes revealed identical molar mass of 50 kDa (estimated by SDS-PAGE) and pI values of 3.5, however, they varied in Km values obtained for Mn2+ oxidation. The addition of wood and straw methanol extracts to the cultures showed that the production of MnPs in wheat-straw cultures was influenced rather by the type of cultivation than by phenolic compounds from lignocellulosic material which induced laccase production. The purified CIM1 MnP was able to decolorize selected azo and anthraquinone dyes more rapidly than laccase Lc1. In vitro dye decolorization showed a synergistic cooperation of MnP and laccase. In the case of CSB degradation MnP prevented from the production of a differently colored substance that could be produced after CSB degradation by laccase-HBT system.
Keywords: lignin; Mycology; Oxidation-Reduction; Peroxidases; Polyporaceae; barva; barvicí látky; Lignin; bakteriální proteiny; peroxidasy; Electrophoresis, Polyacrylamide Gel; pšenice; Azo Compounds; lakasa; Anthraquinones; Drug Synergism; Laccase; azosloučeniny; anthrachinony; Bacterial Proteins; oxidace-redukce; molekulová hmotnost; Color; mykologie; naftalensulfonany; Coloring Agents; Triticum; Molecular Weight; trypanová modř; Trypan Blue; synergismus léků; elektroforéza v polyakrylamidovém gelu; Naphthalenesulfonates